Optimization of School Library Services to Increase Students’ Visiting Interest - Juairiah, Juairiah; Handayani, Fitri (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
This study aims to analyze the optimization of services in a school library. The research employed a descriptive qualitative method, which seeks to describe the results of observations of phenomena as well as credible and valid data sources related to the optimization of school library services. The subject of this study was the library of MAN 1 Banjar, while the object of the study was library visitation at MAN 1 Banjar. The results indicate that library visitation services have not yet been optimized. The average number of visitors per month is approximately 20 people. The conclusion of this study highlights the need to increase the book collection and utilize internet facilities to maximize the number of library visitors. The implication of this study is to provide insights for improving library services in order to increase school library visits.